Procalcitonin in Odontogenic Infection: An Emerging Tool for Clinical Decision-Making - Pahlevi, Muhammad Reza; Anggoro, Hamzah Sukma; Istadi, Didit; Arindra, Pingky Krisna (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2026)
Odontogenic infection is the most common infection of the orofacial area. It can cause sepsis, activate host inflammatory response, and progress to organ failure and death. Patients presenting critical symptoms of sepsis need prompt diagnosis, monitoring, and risk stratification. Therefore, a biomarker specific to bacterial infection is essential for rapid diagnosis, immediate treatment, and saving lives. Procalcitonin is an elevated biomarker in response to bacterial infection; however, its use in oral and maxillofacial surgery is still limited. This review aimed to evaluate the role of procalcitonin as a biomarker in odontogenic infection. Procalcitonin was useful in managing odontogenic maxillofacial infections leading to sepsis, odontogenic deep neck infections, and abscesses. Procalcitonin can also direct antibiotic therapy initiation, escalation, and cessation, reflecting its usefulness in antibiotic stewardship. Future studies should elucidate the optimum cut-off value of procalcitonin in odontogenic infection management and its potential to be combined with other markers.